2022
DOI: 10.29173/ijcc23
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Current Interventions to Alleviate Parental Distress in the NICU: A Rapid Review

Abstract: Background: The birth of a premature infant and admission to the NICU is often unexpected and traumatic for families, leading to increased distress and can negatively impact parental-infant attachment. Appropriate interventions can help to lessen the negative impact of a NICU admission on families, improving parental mental health, reducing distress, enhancing parent- infant relationships, and improving the long-term physical, cognitive, emotional, and social development of the infant. Aims: The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This study further highlights the need for differential support both during the NICU and across the first postpartum year for mothers of premature infants. Interventions addressing anxiety and stress during NICU admission which focus on structured nursing interventions have been successful at reducing anxiety and stress (64), but interventions must now focus, in the first instance, on addressing concerns specific to the postpartum period, and this support must be differential dependent on categories of gestational age. For example, as the results of this study indicated, mothers of later-premature infants score significantly higher on the practical infant care anxieties subscale, and so interventions may wish to target concerns surrounding this, such as feeding and washing.…”
Section: Discussionmentioning
confidence: 99%
“…This study further highlights the need for differential support both during the NICU and across the first postpartum year for mothers of premature infants. Interventions addressing anxiety and stress during NICU admission which focus on structured nursing interventions have been successful at reducing anxiety and stress (64), but interventions must now focus, in the first instance, on addressing concerns specific to the postpartum period, and this support must be differential dependent on categories of gestational age. For example, as the results of this study indicated, mothers of later-premature infants score significantly higher on the practical infant care anxieties subscale, and so interventions may wish to target concerns surrounding this, such as feeding and washing.…”
Section: Discussionmentioning
confidence: 99%